Transcriptional Landscapes of Long Non-coding RNAs and Alternative Splicing in Pyricularia oryzae Revealed by RNA-Seq - Li, Zhigang; Yang, Jun; Peng, Junbo; Cheng, Zhihua; Liu, Xinsen; Zhang, Ziding; Bhadauria, Vijai; Zhao, Wensheng; Peng, You-Liang (Frontiers in Plant Science, 2021)
Pyricularia oryzae causes the rice blast, which is one of the most devastating crop diseases worldwide, and is a model fungal pathogen widely used for dissecting the molecular mechanisms underlying fungal virulence/pathogenicity. Although the whole genome sequence of P. oryzae is publicly available, its current transcriptomes remain incomplete, lacking the information on non-protein coding genes and alternative splicing. Here, we performed and analyzed RNA-Seq of conidia and hyphae, resulting in the identification of 3,374 novel genes. Interestingly, the vast majority of these novel genes likely transcribed long non-coding RNAs (lncRNAs), and most of them were localized in the intergenic regions. Notably, their expressions were concomitant with the transcription of neighboring genes thereof in conidia and hyphae. In addition, 2,358 genes were found to undergo alternative splicing events. Furthermore, we exemplified that a lncRNA was important for hyphal growth likely by regulating the neighboring protein-coding gene and that alternative splicing of the transcription factor gene CON7 was required for appressorium formation. In summary, results from this study indicate that lncRNA transcripts and alternative splicing events are two important mechanisms for regulating the expression of genes important for conidiation, hyphal growth, and pathogenesis, and provide new insights into transcriptomes and gene regulation in the rice blast fungus.